1999
DOI: 10.1159/000006583
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Dye-Coupling of Cells in the Pigeon Isthmo-Optic Nucleus

Abstract: Ground-feeding birds such as pigeons possess the most developed isthmo-optic nucleus in all classes of vertebrates. A previous study showed that this centrifugal or retinopetal nucleus modulates visual activity in tectal cells of pigeons; the present study aimed at revealing the morphology and possible dye-coupling of neurons in the isthmo-optic nucleus and in the ectopic cell region by intracellular injections of Lucifer yellow into neurons in slices. One hundred and twelve successfully labeled cells of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It characteristically consists of small monopolar neurons ∼15 µm in diameter, which in Neognathae with well‐developed ION form a lamina around a central neuropil containing their dendrites (Clarke & Caranzano, ; Cowan, ; Güntürkün, ; Li & Wang, ). The morphologically different ectopic centrifugal neurons, which lie outside the proper ION, are more heterogeneous in size and generally multipolar (Clarke & Cowan, ; Cowan & Clarke, ; Hayes & Webster, ; Li & Wang, ; Médina, Repérant, Miceli, Bertrand, & Bennis, ; O'Leary & Cowan, ; Weidner, Desroches, Repérant, Kirpitchnikova, & Miceli, ; Weidner, Repérant, Desroches, Miceli, & Vesselkin, ; Wolf‐Oberhollenzer, ). The ION presents a high variety of morphologies with different levels of complexity, but in most species (with some noteworthy exceptions such as Procellariiformes and Pelicaniformes) it is at least clearly distinguishable as a nucleus (Gutiérrez‐Ibáñez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It characteristically consists of small monopolar neurons ∼15 µm in diameter, which in Neognathae with well‐developed ION form a lamina around a central neuropil containing their dendrites (Clarke & Caranzano, ; Cowan, ; Güntürkün, ; Li & Wang, ). The morphologically different ectopic centrifugal neurons, which lie outside the proper ION, are more heterogeneous in size and generally multipolar (Clarke & Cowan, ; Cowan & Clarke, ; Hayes & Webster, ; Li & Wang, ; Médina, Repérant, Miceli, Bertrand, & Bennis, ; O'Leary & Cowan, ; Weidner, Desroches, Repérant, Kirpitchnikova, & Miceli, ; Weidner, Repérant, Desroches, Miceli, & Vesselkin, ; Wolf‐Oberhollenzer, ). The ION presents a high variety of morphologies with different levels of complexity, but in most species (with some noteworthy exceptions such as Procellariiformes and Pelicaniformes) it is at least clearly distinguishable as a nucleus (Gutiérrez‐Ibáñez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the neurons are monopolar with flask‐shaped or pyriform somata, 15–25 μm in diameter, from the apical pole of which two to four primary dendritic trunks emerge to divide into parallel branches directed toward the neuropil. Their axons arise either from the opposite basal pole of the cell body or from one of the apical dendritic trunks (Cowan, 1970; Miceli et al, 1995; Li and Wang, 1999a). The NIO also contains a small population of GABAergic interneurons (Miceli et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may imply that tectoisthmic cells are at least in part not those that receive isthmic afferents (Gruberg et al, 1994), but the observed differences could also be due to selective labeling or small sample. Dye-coupling has been found in various brain regions in different species, including, for example, NI in teleosts (Williams et al, 1983) and in amphibians Wiggers, 1998), the optic tectum in amphibians (Wang & Matsumoto, 1990;Wiggers, 1998), the isthmo-optic nucleus in birds (Li & Wang, 1999), and the striatum, neocortex, and hippocampus in rats (Peinado et al, 1993;Onn & Grace, 1994;Velazquez et al, 1997). Dye-coupling has been suggested to be indicative of electrotonic connections (Peinado et al, 1993) and0or of extensive connections via chemical synapses between cells (Wiggers, 1998).…”
Section: Discussionmentioning
confidence: 99%